MAKE A BLOCKTRIS GAME USING TURBO PASCAL - Ahmad Zakie Lutfi; Hariyanto Hariyanto, SKom, MM (Jurnal Sistem Informasi, 2001)
In making this BlockTris, the author tries to explain how made it to explain in outlineonly. And the procedures set forth only the procedures are called directly from themain program. Because the procedures are the most important parts of this BlockTrisGame.BlockTris game is made by using the Turbo Pascal programming language BorlandInc output.